2019
DOI: 10.1002/anie.201813091
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Anion for Ionic Liquid and Battery Electrolyte Applications: Half Triflamide, Half Carbonate

Abstract: The synthesis of a new imide type anion, methylcarbonate(trifluoromethylsulfonyl)imide (MCTFSI) is described and the physicochemical properties of its sodium and N‐butyl‐N‐methyl pyrrolidinium salts as well as structural information obtained by X‐ray diffraction studies of the sodium salt are discussed in terms of charge delocalisation, coordination chemistry and electrochemical behaviour with respect to the analogous imdides bis(trifluoromethanesulfonyl)imide (TFSI) and bis(fluorosulfonyl)imide (FSI). The ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
(74 reference statements)
0
19
0
Order By: Relevance
“…In previous reports, researchers only focused on either the low-temperature behavior of the electrolyte or the roomtemperature performance of the electrode. For example, a cascade of pioneering attempts at establishing composite electrolytes, such as (Pip 13 FSI) 0.5 (Pyr 14 FSI) 0.5 , 11,12 TEATFB/ DOL, 13 and MeEt 3 N + /ACN/DOL, 14 have been geared towards addressing the freezing issue of ILs. However, the estimated energy densities are still unsatisfactory due to volatilization of the solvent, inferior voltage-tolerance or, especially, poor compatibility between the electrolyte and the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, researchers only focused on either the low-temperature behavior of the electrolyte or the roomtemperature performance of the electrode. For example, a cascade of pioneering attempts at establishing composite electrolytes, such as (Pip 13 FSI) 0.5 (Pyr 14 FSI) 0.5 , 11,12 TEATFB/ DOL, 13 and MeEt 3 N + /ACN/DOL, 14 have been geared towards addressing the freezing issue of ILs. However, the estimated energy densities are still unsatisfactory due to volatilization of the solvent, inferior voltage-tolerance or, especially, poor compatibility between the electrolyte and the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…The example of the [MCTFSI] − anion recently investigated by our group as its sodium and [C 4 mpyr] + salts provide further insight into the effect of substituting trifluoro‐ and fluorosulfonyl groups on imide‐type anions with carbonyl based functional groups. The solid–liquid phase transition behavior and short‐term thermal stability for the sodium and pyrrolidinium carbimide salts, examined by DSC and TGA respectively, show values between the corresponding [cation][TFSI] and [cation][FSI] salts.…”
Section: Anion Types and Their Propertiesmentioning
confidence: 99%
“…An assessment of the coordination environment of the recently reported [MCTFSI] − anion in its Li salt cannot be made because crystallographic data are not available. A comparison of Na[MCTFSI] with its [TFSI] − equivalent shows that replacement of one tetrahedral O 2 S‐CF 3 group by a trigonal and less electron withdrawing OC−OCH 3 group leads to significant differences in the Na coordination environment (Figure ).…”
Section: Structural Characterisation Of Neat M(anion)n (M= LI Na) Samentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve a dendrite-free lithium battery, Chen et al 7 designed a heteroatom Si substituent based on an imidazolium TFSI IL, which showed low viscosity and high conductivity values. Gunderson-Briggs et al 26 have also reported a new IL based on a hybrid anion, methyl-carbonate(trifluoromethylsulfonyl)imide (MCTFSI). They investigated the impact of this anion component in electrolytes and ILs and demonstrated the ability of the MCTFSI anion to act as a chelating or monodentate ligand, creating three unique sodium environments in the salt form and making it better coordinating to sodium than the TFSI analogue.…”
Section: Introductionmentioning
confidence: 99%